2020
DOI: 10.3390/ijms21124525
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II, Hypercholesterolemia, and Vascular Smooth Muscle Cells: A Perfect Trio for Vascular Pathology

Abstract: Cardiovascular disease is the leading cause of morbidity and mortality in the Western and developing world, and the incidence of cardiovascular disease is increasing with the longer lifespan afforded by our modern lifestyle. Vascular diseases including coronary heart disease, high blood pressure, and stroke comprise the majority of cardiovascular diseases, and therefore represent a significant medical and socioeconomic burden on our society. It may not be surprising that these conditions overlap and potentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 92 publications
1
19
0
1
Order By: Relevance
“…In the rat model used in this study, at the end of reperfusion Ang II caused massive microvascular leakage along the venular networks, causing interstitial edema and compromising the capillary viability, while ROS formation increased, indicating marked oxidative stress. Our data support previous studies that evaluated the effects caused by angiotensin II in different pathophysiological conditions, such as hypertension and hypercholesterolemia [ 34 , 35 ]. Ang 1-7 did not affect microvascular vessels under baseline conditions, but it was able to reduce extravascular leakage and counteract the increase in ROS.…”
Section: Discussionsupporting
confidence: 91%
“…In the rat model used in this study, at the end of reperfusion Ang II caused massive microvascular leakage along the venular networks, causing interstitial edema and compromising the capillary viability, while ROS formation increased, indicating marked oxidative stress. Our data support previous studies that evaluated the effects caused by angiotensin II in different pathophysiological conditions, such as hypertension and hypercholesterolemia [ 34 , 35 ]. Ang 1-7 did not affect microvascular vessels under baseline conditions, but it was able to reduce extravascular leakage and counteract the increase in ROS.…”
Section: Discussionsupporting
confidence: 91%
“…Cardiovascular diseases in COVID-19 patients involves IL-6, ACE2, and angiotensin as the critical mediators that drive the pathological process. The increased IL-6 from activated macrophages and endothelial and smooth muscle cells after SARS-CoV-2 infection promotes the generation of MCP-1, upregulates the expression of cell adhesion molecules, and motivates the proliferation and migration of vascular smooth muscle cells, thus promoting atherogenesis (St Paul et al, 2020). Therefore, the level of circulating IL-6 may be a risk predictor of cardiovascular events in COVID-19.…”
Section: Protecting Target Organsmentioning
confidence: 99%
“…Meanwhile, by reviewing the literature, it was reported that angiotensin II (Ang II) stimulated a calcium-sensitive tyrosine kinase Pyk2 via the type-1 angiotensin II (AT1) receptor in pulmonary vein endothelial cells (PVECs) and vascular smooth muscle cells (VSMCs) ( Tang et al, 2000 ; Satoh et al, 2001 ; Nakashima et al, 2006 ). In the endothelial cells, Ang II binds to EC receptors and facilitates the expression of plasminogen activator inhibitor-1 and cell adhesion molecules, which may promote the development of atherosclerosis and myocardial infarction ( Luscinskas and Gimbrone, 1996 ; St Paul et al, 2020 ), due to promoting ROS generation, increasing the cell-surface expression of cell adhesion molecules, and enhancing leukocyte adhesiveness to ECs, eventually causing endothelium dysfunction. Would the presence of Ang II and EC injury in the initial stage of atherosclerosis activate the Pyk2/MCU pathway (further aggravating the progression of the disease)?…”
Section: Introductionmentioning
confidence: 99%